Numerical analysis of framed building response to tunnelling induced ground movements. (1st March 2018) - Fu, Jinyang; Yu, Zhiwu; Wang, Shuying; Yang, Junsheng
Highlights: Essential factors affecting framed building response to tunnelling is prioritized. Framed building responses more sensitive on stiffer ground than on softer ground. Interface friction relieves building concave bending but intensify convex bending. Ground stiffness distribution and degradation affect behaviour of building side bay. Abstract: Tunnelling in congested urban area may inevitably induce ground movement causing damage to adjacent surface buildings. Past research usually oversimplified surface structure as an equivalent elastic beam, which is unable to represent behaviour of a framed building realistically due to frame action. In this study, a series of numerical analyses were conducted to investigate the behaviour and damage mechanism of a framed building with individual footing due to tunnelling induced ground movements. Nonlinear behaviour of the infilled wall and the interfaces between soil-structure and between frame-wall were explored to interpret the complex interaction effects in the system. A non-uniform deformation around the tunnel was applied to simulate the realistic tunnelling induced ground movements while the distribution of initial ground stiffness affected by building weight was reproduced by a user defined nonlinear constitutive model. The different responses in terms of angular distortion, horizontal strain and smeared crack pattern of the framed building subject to scenarios with different ground stiffness, interface parameters and different frame infill configurations were evaluated. The results can be practically used to assess the performance of framed building subject to different ground deformation conditions resulting from tunnelling. The presented analysis provided a useful background for properly understanding and prioritizing those factors having a significant effect on the response of framed building to tunnelling induced ground movements.